THE IMPORTANCE OF CHILDREN’S LITERATURE IN RAISING THE YOUNG GENERATION AS ACCOMPLISHED INDIVIDUALS - Makhina Kuchkarova (Web of Journals Publishing, 2025)
The article provides information about the great importance of children's literature, which is an integral part of adult literature, in raising the young generation as perfect people, and that children’s literature is distinguished by the great and complex task of raising the future generation as physically strong, spiritually mature, mentally healthy, with complete faith and belief, knowledgeable, highly spiritual, courageous and patriotic individuals.
Keywords: Children's literature, spiritual mindset, accomplished individual, ideological content, artistic, enlightening ideas, a reader.